Single Nucleotide Polymorphism of IL-2 Gene at Position +166 in Type 1 Diabetes of Iraqi Patients - Ibtesam, B. Hassan (University of Thi-Qar Journal of Science, 2020)
The present study aimed at investigating of frequency of polymorphism of interleukin-2 gene (IL2) at position+166 SNP) in Type 1 Diabetes and in healthy controls subjects 39 of Iraqi patients, (12 males & 27 females;1 5.65 ± 1.79 years) and 21 controls.(7 mail & 14 female ; 14.66 ± 3.43 years) attended the hospital in Baghdad for diagnosis and treatment during the period February 2015 – January 2016 were enrolled in this study, the polymorphism of IL2+166 was data waved by polymerase chain reaction-specific sequence primer (PCR-SSP) assay. The results showed a comparison IL2+166 genotypes & alleles between T1D patients & controls frequencies of TT genotype & T allele (71.69vs. 68.95%;P =0.589 respectively) There was a significant increase in patients contrast to controls, (51.38vs. 48.08%; P =0.312) and associated RR rates were 19.2% & 27.0%, respectively. And the related EF values were 1.56 & 1.60 .Similar observations were made in GG genotype. In contrast TG genotype & G allele (23.93 vs. 28.55%,P =1.000 respectively) Low frequency was observed in patients compared to healthy subjects (43.28 vs. 43.22%; P =0.312), and the related PF values were 0.56 & 0.62 , respectively. The results of the study indicate that IL2+166 SNP may have a role in the mechanism of etiopathogenic of T1D in the samples of Iraqi patients